2021
DOI: 10.3390/nu13072460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low FODMAPs Diet on Irritable Bowel Syndromes: A Systematic Review and Meta-Analysis of Clinical Trials

Abstract: We conducted a meta-analysis exploring the effect of a low fermentable oligo-, di-, monosaccharides, and polyols diet (LFD) on the overall symptoms, quality of life, and stool habits of irritable bowel syndrome (IBS) patients. The meta-analysis was performed using a random-effects method. The effect size was presented as weighted standardized mean difference (SMD) and 95% confidence interval (CI). Subgroup analyses were conducted to determine the potential effects of covariates on the outcome. Twenty-two paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…A meta-analysis by Hahn et al. 11 further demonstrated that a low FODMAP diet was useful in improving IBS symptoms, a finding supported by accumulating evidence. 39,40 However, the decreased function of the sucrase-isomaltase complex involved in sucrose and starch degradation is reportedly related to IBS pathophysiology.…”
Section: Pathophysiology Of Ibsmentioning
confidence: 88%
See 2 more Smart Citations
“…A meta-analysis by Hahn et al. 11 further demonstrated that a low FODMAP diet was useful in improving IBS symptoms, a finding supported by accumulating evidence. 39,40 However, the decreased function of the sucrase-isomaltase complex involved in sucrose and starch degradation is reportedly related to IBS pathophysiology.…”
Section: Pathophysiology Of Ibsmentioning
confidence: 88%
“…Among the articles published during the search period, we selected 18 papers of interest related to the pathophysiology and treatment of IBS and explained the contents of these articles. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pathophysiology of IBS Genetic factors are involved in the pathology of IBS. 20 A comprehensive analysis of colonic mucosal microRNAs was performed by Mahurkar-Joshi et al 2 The authors performed reverse transcription polymerase chain reaction on biopsy specimens of the sigmoid colons of IBS patients and healthy participants to study genes that were differentially expressed between IBS patients and healthy controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies assessing the LFD have focussed on the initial short-term elimination phase, with a large number of RCTs demonstrating its efficacy (Table 2). Recent meta-analyses, which pooled outcome data amongst studies that used IBS-SSS to assess clinical response, demonstrated a mean reduction of around 50 points following the LFD [42,43]. It is worth noting that studies assessing the LFD have had variable comparator diets, such as a sham diet, habitual diet, TDA, Australian diet and high FODMAP diet, highlighting the heterogeneity of studies to date [44].…”
Section: Low Fodmap Dietmentioning
confidence: 99%
“…IBS and GERD have been reported in about one-third of patients with each disease [ 9 , 10 ]. Meta-analysis of randomized controlled studies supported the benefit of consuming a low FODMAPs diet on gastrointestinal symptoms and quality of life in patients with IBS [ 11 , 12 ]. However, the role of carbohydrates on GERD has not been well understood.…”
Section: Introductionmentioning
confidence: 99%